The impact of IT application on supply chain learning and service performance. Issue 1 (7th November 2019) - Huo, Baofeng; Haq, Muhammad Zia Ul; Gu, Minhao
Abstract : Purpose: Despite the recognition that supply chain (SC) learning is important for competitive advantage, little is known how to enable such learning. The purpose of this paper is to examine the effects of information technology (IT) application on different types of SC learning (i.e. internal, customer and supplier learning) and service performance. Design/methodology/approach: This study applies structural equation modeling to test the conceptual model based on data collected from 213 manufacturing firms in China. Findings: Although strategic application has a direct and negative relationship with all three dimensions of SC learning, it indirectly and positively improves SC learning through tactical and operational application. The authors observe that tactical application is positively related to all three dimensions of SC learning, while operational application improves internal and customer learning only. The authors also notice that internal and customer learning are positively related to service performance. Research limitations/implications: This study classifies IT application into strategic, tactical and operational dimensions, which may not adequately cover the entire set of IT application portfolio. Practical implications: The findings suggest managers to use corresponding IT application to improve SC learning and service performance. Originality/value: This study provides a new framework to understand the relationships between IT application, SC learning and service performance.